Validation of the Arabic version of the client satisfaction with device module of the “orthotics and prosthetics users” survey - Hadeel Bakhsh; Franco Franchignoni; Elisabetta Bravini; Giorgio Ferriero; Andrea Giordano; Calogero Foti (Annals of Saudi Medicine, 2014)
BACKGROUND AND OBJECTIVES: Assessing patient satisfaction with orthosis (PSwO) is a key point for clinical practice to increase a patient's adherence to therapeutic programs and reduce orthotic-related costs. The Client Satisfaction with Device (CSD) module of the Orthotics and Prosthetics Users' Survey (OPUS) is one of the most widely-used questionnaires for assessing PSwO, but its validated version in the Arabic language is lacking. The objective of this study is to generate and psychometrically validate an Arabic version of the CSD (CSD-Ar). DESIGN AND SETTINGS: This is a cross-sectional study, conducted during February to June 2013 at 2 inpatient and outpatient rehabilitation departments in Riyadh, Saudi Arabia. PATIENTS AND METHODS: Translation of CSD-Ar was carried out according to the guideline recommendations of Linacre. A convenience sample of 100 orthotic-user patients with various conditions (59% men, mean age 36 years) completed the CSD-Ar. Data were analyzed using exploratory factor analysis followed by Rasch analysis. RESULTS: Factor analysis confirmed the unidimensionality of the CSD-Ar. Rasch criteria for the functioning of rating scale categories were fulfilled. All items showed an adequate fit to the Rasch model. The person separation reliability was .75 and Cronbach alpha .83. There was a borderline local dependency between items 1 (“My device fits well”) and 3 (“My device is comfortable throughout the day”). CONCLUSION: The internal construct validity of the CSD-Ar in Arab patients with various types of orthotics has been confirmed. This study provides a useful starting point for the use of this outcome measure in Arabic-speaking countries.